Non‐uniform nanosecond gate‐delay of hybrid pixel detectors. (17th August 2017) - Shayduk, Roman; Pennicard, David; Krausert, Konstantin; Gaal, Peter; Volkov, Sergey; Vonk, Vedran; Hejral, Uta; Jankowski, Maciej; Reinhardt, Matthias; Leitenberger, Wolfram; Stierle, Andreas
Abstract : The gating uniformity of Pilatus area X‐ray detectors was characterized using synchrotron radiation. Gating offsets of more than 15 ns were observed between different modules of a Pilatus300K‐W detector. Abstract : A simple experiment to characterize the gating properties of X‐ray area detectors using pulsed X‐ray sources is presented. For a number of time‐resolved experiments the gating uniformity of area detectors is important. Relative gating delays between individual modules and readout chips of PILATUS2 series area X‐ray detectors have been observed. For three modules of a PILATUS 300K‐W unit the maximum gating offset between the modules is found to be as large as 30 ns. On average, the first photosensor module is found to be triggered 15 ns and 30 ns later than the second and the third modules, respectively.